Implementasi Diorama untuk Meningkatkan Kreativitas Belajar Siswa dalam pembelajaran IPAS pada Kelas VIII di MTS Miftahul Huda - Zumrudah, La’la’a Alfi; Rahman, Rifki Ramanda; Kafili, Saila Mizab Rifdal; Chakim, Muhammad Fani; Nur, Dany Miftah M. (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to implement diorama media in Natural and Social Sciences (IPAS) learning to increase student creativity at the Madrasah Tsanawiyah Miftahul Huda Lodan. The approach used is a design research method, which involves the development and repeated testing of the use of dioramas as a learning tool. This research was carried out through several stages, namely: problem identification, diorama design, implementation, evaluation and revision based on feedback from teachers and students. Data was collected through observation, interviews, and assessing student creativity before and after the intervention. The research results show that the use of dioramas significantly increases student involvement and creativity in the learning process, especially in critical thinking, imagination and problem solving skills. Thus, diorama media has proven to be effective as an innovative learning tool to increase student creativity in science classes.